2017
DOI: 10.1111/nmo.13074
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic stress‐induced persistent changes in DNA methylation regulate neuropeptide Y expression in rat jejunum

Abstract: These results suggest that DNA demethylation could be operative as an epigenetic mechanism in the long-term regulation of NPY gene expression to alter the gut motility during traumatic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Gastrointestinal function is closely related to the level of fatigue in CFS patients. Relevant research shows that the patient with CFS has intestinal barrier dysfunction, gut immune dysfunction, altered gut motility, altered gastrointestinal secretion, altered intestinal flora, and altered gut-brain axis [35,36].These changes make CFS patients prone to diarrhea, abdominal pain, constipation and other digestive symptoms [37][38][39][40][41]. At the same time, some studies found that abnormal alteration to intestinal flora are linearly related to decreased motivation, increased levels of fatigue, anxiety, depression in CFS patient [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal function is closely related to the level of fatigue in CFS patients. Relevant research shows that the patient with CFS has intestinal barrier dysfunction, gut immune dysfunction, altered gut motility, altered gastrointestinal secretion, altered intestinal flora, and altered gut-brain axis [35,36].These changes make CFS patients prone to diarrhea, abdominal pain, constipation and other digestive symptoms [37][38][39][40][41]. At the same time, some studies found that abnormal alteration to intestinal flora are linearly related to decreased motivation, increased levels of fatigue, anxiety, depression in CFS patient [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The rat model with closed head diffused brain injury was employed to induce rMTBI, as described previously [9,14,15,44]. To induce rMTBI, the rats were subjected to 5 hits of MTBI on alternate days over 9 days.…”
Section: Repeated Mild Traumatic Brain Injurymentioning
confidence: 99%
“…The mRNA expression of the HDACs, CBP, and CREB was estimated using RT-qPCR, as described previously [14,15,44]. The total RNA from the Arc tissues was isolated using the TRIzol (Ambion, Austin, TX, USA) method, and the DNA contamination was removed using the DNA-free TM DNA Removal Kit (Life Technologies, Carlsbad, CA, USA).…”
Section: Rt-qpcr For Mrna Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several psychological and physiological disturbances following TBI are known to be sufficient to alter the balance of gut homeostasis maintained by the microbial ecosystem and host immune system, with results including traumatic stress 5 , dysfunctional intestinal contractility and motility 6,7 , and increased gut permeability 8 . Accordingly, animal studies have revealed profound changes in gut microbiota after various nerve injuries 6,7 , such as stroke spinal cord injury 8 and TBI 4,5 . More importantly, gut dysbiosis in animal models is not merely a byproduct of injury but an essential contributory factor to TBI-related neuropathology and impaired behavioral outcomes 9 .…”
Section: Introductionmentioning
confidence: 99%